The Pengaruh Ukuran Perusahaan, Likuiditas, Profitabilitas, dan Solvabilitas Terhadap Opini Audit Going Concern pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020 - Maria Cristanti Nababan; Otto Ruth Sonya Damanik; Maghfirah Maghfirah; Keumala Hayati (Owner : Riset dan Jurnal Akuntansi, 2022)
The continuity of the compant’s business among the various risk that arise as a result of internal or external factors are the expectations of all entities in effort to achieve  the company’ goals. The purpose of this study is to find out what the effect of company size, liquidity, solvency and profitability on Going Concern audit opinion of manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Secondary data is used from the Indonesia Stock Exchange, the source of data is from www.idx.co.id. In this study, the sampling method selected according to the purposive sampling method was used and 44 companies were selected as samples. Data analysis using Logistic Regression test. The results showed that the size, liquidity, profitability and solvency of the company affected the Going Concern audit opinion.